Imaginaire de crise dans la planification du RTE-T UE - Noam Greco Monteiro (EchoGéo)
This article demonstrates how transport planning by EU institutions has evolved from an open planning imaginary, shaped by the end of the Cold War and the potential for integration through international trade, to a context of multiple crises that has prompted a rethinking of the territorial imaginary in the planning of Trans-European Transport Networks (TEN-T). At its inception, the Trans-European Transport Networks (TEN-T) was confined to the member countries. However, since its establishment in 1992, the possibility of extending it to third countries has been contemplated. This article presents new chronological data on the expansion of the TEN-T to third countries, thus supplementing the existing research on this topic. It demonstrates that geopolitical considerations were pivotal in shaping the spatial manifestation of the TEN-T's vision for the future.